Inflasi Dalam Ekonomi Islam: Analisis Konseptual Dan Pendekatan Pengendaliannya - Adriansyah, Henry Martin (Multidisciplinary Journal of Religion and Social Sciences, 2026)
Inflation is a financial phenomenon that is a major concern in a global context. From an Islamic perspective, the view of inflation is not only economic but also encompasses profound moral and ethical dimensions. This study seeks to provide a comprehensive overview of inflation from an Islamic perspective, encompassing its definition, causes, impacts, and solutions in line with Islamic economic principles. Through a qualitative approach with document and literature analysis, the study investigates the concept of inflation in Islam and its implications for Muslim societies. The discussion explores the causes of inflation from an Islamic perspective, including usury (interest), market instability, and unequal distribution of wealth. It also analyzes the impact of inflation on society, such as unfair redistribution of wealth and declining purchasing power. Finally, the study outlines proposed Islamic solutions to address inflation, such as regulating the financial system in accordance with Sharia law, controlling production and equitable distribution, and promoting morally based economic education. With a deeper understanding of inflation from an Islamic perspective, it is hoped that the solutions implemented can address the problem of inflation effectively and fairly, in accordance with religious values.